Discovery of 2, 4-diarylaminopyrimidine derivatives bearing dithiocarbamate moiety as novel ALK inhibitors. (15th July 2022) - Wang, Xinyue; Hu, Yiran; Zou, Xinyu; Wang, Pengfei; Yue, Hao; Guo, Mingzhang; Li, Zefei; Gong, Ping
Graphical abstract: Abstract: To overcome drug resistance caused by ALK kinase mutations especially G1202R, two series of novel 2, 4-diarylaminopyrimidine derivatives bearing dithiocarbamate moiety were designed, synthesized and evaluated for their biological activities. Among all the target compounds, B10 efficiently inhibited the proliferation of ALK-positive Karpas299 and H2228 cells both with IC50 values of 0.07 μM. In addition, B10 exhibited remarkable enzymatic inhibitory potency with IC50 values of 4.59 nM, 2.07 nM and 5.95 nM toward ALK WT, ALK L1196M and ALK G1202R, respectively. Furthermore, B10 induced apoptosis in H2228 cell and caused cell cycle arrest in G2/M phase. Ultimately, the binding modes of B10 with ALK WT and ALK G1202R were ideally established, which further confirmed the structural basis in accordance with the SARs analysis. These results indicated that B10 was a potent ALK inhibitor for ALK G1202R mutation treatment and deserved for further investigation.